Opportunities and some results of measuring cultural capital in sociological research practice - Nechitailo, I.; Nazarkin, P.; Biriukova, M.; Stadnik, O.; Boriushkina, O.; Rozova, O. (My University, 2022)
The article is devoted to the problem of measuring cultural capital in modern sociological practice. Following J. C. Alexander, authors focus on the significance of cultural structures in individuals' and groups' lives, which actualizes the need for a more detailed study of them. The purpose of the article is to identify indicators for cultural capital measuring and present empirical research results, which is an attempt to verify these indicators. Based on the results of studies by P. DiMaggio, C. J. Crook, N. D. De Graaff, such indicators of cultural capital are highlighted as the frequency of visits to theaters and cinemas, concerts of classical and contemporary music, museums, exhibitions, etc.; having a home library; the frequency of reading books, Internet articles, news, etc. These indicators, at the same time, are the resources of accumulation of certain types of cultural capital such as "status" and "knowledgeinformation" (author's typology). The results of measurements of the cultural capital of Ukrainian students using the above indicators are presented. It is concluded that the transmission of status cultural capital and the knowledge-information cultural capital is a powerful factor in influencing the processes of personal development and academic success of students.
Keywords: сultural capital; сultural structures; empirical indicators; empirical research; students of Ukraine